Analisis Penerapan Pembiayaan Murabahah Pada Fatwa No. 84/DSN-MUI/XII/2012 Bank Muamalat Kantor Cabang Darmo Surabaya - Diah Putri Pravita Sari; Sri Herianingrum (Universitas Airlangga, 2014)
This study aims to determine the theoretical and practical application of murabahah about how the application by the Muamalat Bank branches of Darmo Surabaya.Methods of research of This study used a qualitative approach with the case study methods and descriptive analyzes. Then the researchers took the data in PT Bank Muamalat with some informants to be interviewed in depth, observed, and the data validated by triangulation methode.These results indicate that the implementation of the bank Muamalat Murabahahdarmo Surabaya branch office in according with the contained in the fatwa of murabahah which stated selling price to the buyer, then the flow of murabahah transaction can not be implemented in accordance with the provisions contained in fatwa because the field of business in Indonesia is still limited, it is not appropriate , next is the method in recognizing income / margin in the murabahah using the annuity method so that implementation of Muamalat bank financing is suitable with the fatwa number 84. REFERENCESAntonio, M Syafi’i. 2008. DasarDasarManajemen Bank Syariah. Jakarta. Gema Insani Press.Basrowi dan Suwandi. 2008. Memahami Penelitian Kualitatif. Jakarta: Rineka Cipta.Dewan Syariah Nasional. 2012. Fatwa Dewan Syariah Nasional Metode Pengakuan Keuntungan Tanwil Bi AlMurabahah Di Lembaga Keuangan Syariah. Jakarta:Fatwa DSN-MUI No. 84.Karim, Adiwarman. 2004. Bank Islam Analisis Fiqih dan Keuangan, Jakarta: III Indonesia.Karim, Adiwarman. 2008. Bank Islam Analisis Fiqh dan Keuangan. Jakarta: Raja grafindo Persada.Rahmawaty, Anita. 2007.